2023
DOI: 10.3390/ijms25010496
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model for Acute Myeloid Leukemia Relapse Using the SORE6 Reporter

Justine Lai,
Chuquan Shang,
Will Chen
et al.

Abstract: Many patients diagnosed with acute myeloid leukemia (AML) relapse within two years of the initial remission. The biology of AML relapse is incompletely understood, although cancer stem-like (CSL) cells have been hypothesized to be important. To test this hypothesis, we employed SORE6, a reporter designed to detect the transcriptional activity of the embryonic stem cell proteins Oct4 and Sox2, to identify/purify CSL cells in two FLT3-mutated AML cell lines. Both cell lines contained ~10% of SORE6+ cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We recently found that purified SORE6 + cells derived from MOLM−13 and MV4−11, two AML cell lines carrying FLT3-ITD, displayed significantly higher CSL phenotype (such as resistance to Ara-C) compared to SORE6 − cells [ 13 ]. Using SORE6 − /SORE6 + cells derived from MOLM−13, we found that the Ara-C inhibitory concentration at 50% (IC50) for SORE6 + cells was 172.9 nM, which is significantly higher than that of their SORE6 − counterparts (61.0 nM, p < 0.0001) ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently found that purified SORE6 + cells derived from MOLM−13 and MV4−11, two AML cell lines carrying FLT3-ITD, displayed significantly higher CSL phenotype (such as resistance to Ara-C) compared to SORE6 − cells [ 13 ]. Using SORE6 − /SORE6 + cells derived from MOLM−13, we found that the Ara-C inhibitory concentration at 50% (IC50) for SORE6 + cells was 172.9 nM, which is significantly higher than that of their SORE6 − counterparts (61.0 nM, p < 0.0001) ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…We recently generated an in vitro model with features mimicking AML relapse [ 13 ]. Specifically, an ‘in vitro remission state’, defined by the absence of trypan blue-negative cells induced by the lowest required dose of Ara-C, is followed by regeneration of AML cells (i.e., ‘in vitro relapse’) after a period of time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations